2022
DOI: 10.1161/jaha.121.025236
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Polygenic Risk Score for Coronary Artery Disease as a Risk‐Enhancing Factor in the Pooled Cohort Equation: A Cost‐Effectiveness Analysis Study

Abstract: Background Cardiovascular diseases are the leading cause of death in the United States, yet a significant proportion of adults at high risk remain undetected by standard screening practices. Polygenic risk score for coronary artery disease (CAD‐PRS) improves precision in determining the 10‐year risk of atherosclerotic cardiovascular disease but health benefits and health care costs associated with CAD‐PRS are unknown. We examined the cost‐effectiveness of including CAD‐PRS as a risk‐enhancing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…It is noted that the performance of various PRSs are similar for CAD and other diseases [8] , [13] . Our results, together with a newly published study demonstrating improved quality-adjusted life-years by implementing PRS [14] , suggest PRS is a cost-effective risk-enhancing factor.…”
supporting
confidence: 63%
“…It is noted that the performance of various PRSs are similar for CAD and other diseases [8] , [13] . Our results, together with a newly published study demonstrating improved quality-adjusted life-years by implementing PRS [14] , suggest PRS is a cost-effective risk-enhancing factor.…”
supporting
confidence: 63%
“…In the grid search for time windows t and embedding dimension d, cosine similarity for 430,579,185 pairs of codes among 29,346 unique codes were calculated for each time window and embedding dimension combination. Ten t time windows (1,2,7,10,14,20,30,40,50, and 60 days) and twelve d embedding dimensions (10,30,50,100,150,200,250,300,350,400,450, and 500) were evaluated. This results in a total of 120 concept-AUC calculated to evaluate the concept derived from NLP in EHR data that are clinically applicable.…”
Section: Evaluation Of Nlp Derived Medical Code Embeddings and Parame...mentioning
confidence: 99%
“…Multiple studies have shown that using a PRSa weighted sum of genetic effects on certain diseases or traits across the human genomecan enhance disease prediction and further improve early prevention 6,18 . Multiple efforts have been made to summarize genetic and clinical information to identify high risk patients, but integrating high-dimensional genome-wide association study (GWAS) and electronic health record (EHR) in heart failure prediction models has not been previously evaluated [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, personal human genome information is useful for personalized medical treatment not only for monogenic diseases but also for polygenetic diseases, e.g., type two diabetes and cardiovascular artery diseases (CAD). Statin prevention therapy for individuals with high CAD genetic risk (polygenic risk score; PRS) was estimated to reduce the mean cost per individual and improve quality‐adjusted life years and averted future events of CAD 3 . The polygenic risk score is usually calculated by summing the multiplied values of the weight, i.e., the beta value from a genome-wide association study from an independent population matched CAD cohort study, and the genotype, e.g., 0, 1, or 2, in each individual.…”
Section: Introductionmentioning
confidence: 99%